Cashless in UUM: factors influencing user's intention to use digital payment based on kiple pay - Pan, Jing Rui (2018)
Digital payment (cashless payment) has huge potential to achieve cashless transaction all around the world by providing digital payment choices where payment is made using cards (credit and debit), E-wallets, mobile payments, electronic cash systems and so on. Digital payment will be a trend in the future. Malaysia is moving towards becoming a cashless society in 2050. While, 78% of Malaysians use mobile devices, only 34% of people use digital payment to purchase products or services. This means that the proportion of digital payments usage is still very low. Therefore, the purpose of this study is to examine the factors that influence user’s intention to use digital payment, with a specific focus of Kiple Pay system, using Technology Readiness and Acceptance Model (TRAM). Four independents variables, optimism, innovativeness, discomfort, and insecurity were applied to examine the perceived usefulness of Kiple Pay. One mediator, perceived usefulness (PU) was used to investigate the intention to use Kiple Pay. The results of current research confirmed that optimism, innovativeness and discomfort have significantly positive with perceived usefulness of Kiple Pay. On the other hand, the study found that insecurity has insignificant with perceived usefulness of Kiple Pay. Furthermore, there is a significantly positive relationship between perceived usefulness and intention to use Kiple Pay.